2016
DOI: 10.15376/biores.11.4.9912-9921
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Polyphenolic Substances Extracted From Spruce (Picea abies) Bark by Microwave-Assisted Extraction

Abstract: Closed-system microwave-assisted extraction was applied to extract total phenolics from spruce (Picea abies) bark, using 96.6% ethanol as an extractant. The influence of particle size (0.3; 1.0; 2.5 mm), time (3 to 20 min), and temperature (60; 80; 100 °C) on polyphenol recovery was also studied. Higher extraction temperature and smaller particle size resulted in a higher yield of extracted polyphenols. However, the effect of extraction time on yield was more complicated. The effect of all three factors is ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
8
1
Order By: Relevance
“…Sládková A. et al conducted a study on P. abies bark extracts attained by MAE, indicating a maximum TPC of 321.1 mg GAE per 100 g dry bark. Although these results showed a lower yield of phenolic compounds compared to our results for the extracts obtained by MAE, it must be mentioned that a different MAE protocol was used [ 46 ].…”
Section: Resultscontrasting
confidence: 81%
“…Sládková A. et al conducted a study on P. abies bark extracts attained by MAE, indicating a maximum TPC of 321.1 mg GAE per 100 g dry bark. Although these results showed a lower yield of phenolic compounds compared to our results for the extracts obtained by MAE, it must be mentioned that a different MAE protocol was used [ 46 ].…”
Section: Resultscontrasting
confidence: 81%
“…The particle size of the matrix also has an important impact on the overall extraction efficiency. The particle size of spruce bark in the range 1–1.4 mm, as used for the experiment, was determined based on our previous research [23,35]. The obtained results have shown that, to achieve a higher yield, particle size should be greater than 0.3 mm and smaller than 2 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation method can provide a simple way to separate the desired extractives from components of the matrix while keeping the original matrix usable for ultimate energy production. Based on the literature survey, the following extraction methods have been investigated for phytochemicals: Solvent extraction ultrasound-assisted extraction (UAE) [18,19], supercritical fluid extraction (SFE) [20,21], microwave-assisted extraction (MAE) [22,23], accelerated solvent extraction (ASE) [24], and subcritical water extraction (SWE) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…These wastes consist of stems of the crop plants like wheat, rice, sugarcane, etc. [3]. Some statistics presented by different authors show that there are large amounts of wastes generated from agro-forestry sector: 709 million tonnes of wheat straw, 673 million tonnes of rice straw, 102 million tonnes of bagasse [4], 0.1 million tonnes of coir [5], and 2.96 million tonnes of solid olive waste [6].…”
Section: Introductionmentioning
confidence: 99%